KEHARMONISAN RUMAH TANGGA TANPA ANAK DI KOTA JAYAPURA: The Harmony Of Childless Households In Jayapura City - BAMBANG, BAMBANG EDI TILARSONO; Hendra, Hendra Yulia Rahman; Musyafa, M. Musyafa (ISTIDLAL, 2024)
This study examines the harmony of childless households in Jayapura City. Although having children is often considered essential for creating a happy family, many couples live harmoniously despite not having children. The purpose of this research is to understand how these couples maintain their harmony and to identify the strategies they use. This study is an empirical research that employs a qualitative approach and a case study method in Jayapura City, Papua. Data were collected through observation, interviews, and documentation. The collected data were then analyzed using descriptive analysis methods and deductive reasoning, and were examined based on Islamic law and family psychology. The validity of the data was tested through triangulation to ensure the accuracy and reliability of the research results. The conclusions of this study are: (a) A harmonious family is one that accepts each partner as they are, supports each other, provides a sense of security and trust, encourages its members to grow and learn from daily experiences, has a solid relationship, creates happiness, faces challenges together, and serves as a source of comfort and motivation. (b) The strategies employed by these couples include: first, maintaining a positive attitude and praying; second, undergoing pregnancy programs and medical consultations; third, supporting and understanding each other; fourth, maintaining communication and attention; fifth, providing support and presence; sixth, keeping pets and staying occupied with work. The implication is that a harmonious family requires a strong foundation of acceptance, support, open communication, and joint efforts to overcome challenges, with positive strategies, maintaining close relationships, and dedication to growing and sharing happiness in their life journey together.